(3GdGSJPcGQ dePGgH YdeGA GdGeUGQ ajeG JVefg GdehWC ef eYGfi GdQCi hGdCKGQs - (3jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj GdeGdcj, GHf YHO GdHQ , CHh YeQ , J (B463 (3g` s; (3CHh YeQ jhSa Hf YHO Gddg, GHf YHO GdHQ GdfeQj GdbQWHj,J (B463 (3g` s
(3ChdgG (B:s
(3HGH GdbVGA HGdjejf eY GdTGgO Cf QShd Gddg Udi Gddg Ydjg hSde bVi HGdjef eY GdTGgO efcQkG gPG GdMOjK ai GdehWC s
(3BNQgG (B:s
(3jfJgi CKfGA HGH CSeGA GdfHi Udi Gddg Ydjg hSde s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs